IMPLEMENTATION OF GOOGLE CLASSROOM APPS TO IMPROVE CREATIVE WRITING SKILLS - Syahruddin Syahruddin; M. Agus; Amal Akbar (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
The purpose of this research is to describe the implementation of the Google Classroom application to improve creative writing skills in students of the PGSD FKIP Unismuh Makassar study program. This research is a quantitative research. The research sample is 30 people. The instruments to be used in this research are: observation notes, questionnaires and performance tests. The data obtained were analyzed using quantitative descriptive analysis using the SPSS 25.0 for windows program. Based on the research results, it is known that there is an increase in creative writing learning outcomes of 23.98%. These results indicate that the Google Classroom application can improve creative writing learning outcomes and improve student performance in online learning.